+0  
 
0
57
1
avatar

If there exists a matrix A such that

\( \mathbf{A} \begin{pmatrix} 1 \\ 0 \\ 0 \end{pmatrix} = \begin{pmatrix} -3 \\ 4 \\ 0 \end{pmatrix},\mathbf{A} \begin{pmatrix} 0 \\ 1 \\ 1 \end{pmatrix} = \begin{pmatrix} 1 \\ 2 \\ 3 \end{pmatrix}, \mathbf{A} \begin{pmatrix} 1 \\ 1 \\ 1 \end{pmatrix} = \begin{pmatrix} 3 \\ 2 \\ 1 \end{pmatrix}\)

calculate \(\mathbf{A} \begin{pmatrix} 1 \\ -1 \\ -1 \end{pmatrix}.\)

 Mar 16, 2020
 #1
avatar
0

\(\mathbf{A} \begin{pmatrix} 1 \\ -1 \\ -1 \end{pmatrix} = \mathbf{A} \begin{pmatrix} 1 \\ 0 \\ 0 \end{pmatrix} - \mathbf{A} \begin{pmatrix} 0 \\ 1 \\ 1 \end{pmatrix} = \begin{pmatrix} -3 \\ 4 \\ 0 \end{pmatrix} - \begin{pmatrix} 1 \\ 2 \\ 3 \end{pmatrix} = \begin{pmatrix} -4 \\ 2 \\ -3 \end{pmatrix}\)

.
 Mar 17, 2020

21 Online Users

avatar
avatar
avatar